Analgesic and Anti-inflammatory Activities of Flower Extracts of Punica granatum Linn. (Punicaceae) - Mithun Sarker, Sreedam Chandra Das, Sajal Kumar Saha, Zobaer Al Mahmud, Sitesh Chandra Bachar (Journal of Applied Pharmaceutical Science)
Punica granatum has been used for centuries to confer health benefits in a number of inflammatory diseases. Based on its usage in Ayurvedic and Unani medicine, dietary supplements containing pomegranate extract are becoming popular for the treatment and prevention of arthritis and other inflammatory diseases. Pet-ether, dichloromethane and methanol fractions of flower part were chosen for pharmacological screening and analgesic and anti-inflammatory activities in animal model. The anti-inflammatory activity was assessed using the carrageenan-induced rat paw edema model. The analgesic effect was measured in mice using the acetic acid-induced writhing test. In the acetic acid-induced writhing test in mice, pet-ether, dichloromethane and methanol fractions at 200 mg/kg doses level showed 75.77% (p
Keywords: Punica granatum,punicaceae,analgesic,anti-inflammatory and carrageenan.